Model for efficient service delivery in public service - Khalil, Samihah; Adelabu, Salihu Abdulwaheed (Macrothink Institute, 2012)
This paper aims to design a modified model for efficient and effective service delivery by governments’ ministries, departments and agencies (MDAs).There are several existing models on service delivery, but it is noted that those models emphasized more on the estimates voted for social/welfare services and the outcomes of services provided by MDAs. Other variables such as managerial accountability and leadership quality are less emphasized.This paper therefore designs a modified model that integrates funding/management of resources, managerial accountability and leadership quality cum structure in order to ensure adequate, efficient and effective service delivery by MDAs of various governments.There seems to b e a strong relationship between these variables in respect of service delivery. Lastly, the paper is conceptual in nature, which gives room for critique by practioners, researchers, scholars and public administrators in lieu of service delivery.